Franciscans of Lithuania in the Years 1940–1989/2014: From Dispersal to Rebirth - Baleišaitė-Sabakonienė, Rasuolė (Lietuvos istorijos studijos, 2016)
The Franciscan Friars from the very first contacts with Lithuania were known as active apostles and educators. With years their influence increased, and at the dawn of the czarist rule the Franciscan life in Lithuania flourished. Unfortunately, the government of the Czar closed all friaries except the one in Kretinga. Just after the vision of revivification in 1912, the year 1940 with the ocupations brought straits again. Analysis of the Franciscan life in Lithuania under the Soviet occupation suggests the division of it into several stages. The year 1940 might be seen as the first break point when repressions against active Friars started to take place. Already in the middle of the 1950s all the frontier office went to the underground, and the last provincial withdrew to Germany. The beginning of the second stage in 1948 marks the repeal of the legal religious orders and the thresthold of the underground life. As no active life could be pursued in Lithuania, all activity of the Friars resettled on the other side of the Atlantic. The third stage dates back to 1980 when the last Franciscan priest in Lithuania P. Puodžiūnas died and two priests – J. Pačinskas and B. Racevičius – received the permission to give vows to one another. The revival was strongly influenced by Franciscan missions that were commenced in 1984. The official breakout from the underground – highlighting the beginning of the fourth stage – coincides with the Mess celebrated on 19th November 1989 in Kretinga. The time between 1989 and 2004 was the regeneration of the Franciscan tradition, establishment of a new vision, building up communities by the newly regained friaries. And though the Provincial curia was re-established in Kretinga in 1997, the culmination of the revival of the Lithuanian Franciscans could be seen on 8th December 2004 when the decree of the Minister General of the Order of Friars Minor came into force, proclaiming the independent province of St. Casimir with all rights.